An unusual presentation of daily headache: A case report (Indian Journal of Case Reports, 2020)
Headache is a fairly common universal symptom caused by multiple etiologies. More than 90% of headaches are primary headaches which are tension-type headaches and migraines. The rest are secondary headaches that have an underlying local or systemic cause. Most often, there could be underlying psychopathology, where the headache would be the presenting symptom. Life stresses, depression, anxiety, and relationship issues are often seen in headache patients. We report a case that was referred to psychiatry from the medicine outpatient department for tension-type headache but had an underlying organic etiology, though it was detected only after thoroughly evaluating the patient with liaison with neurology and ear, nose, and throat doctors.